Resistência de genótipos de soja ao nematoide reniforme em ambiente controlado - de Melo, Carlos Lasaro Pereira; dos Santos, Wanderléia Rodrigues [UNESP]; Asmus, Guilherme Lafourcade (FapUNIFESP (SciELO), 2013)
The aim of this study was to characterize the resistance to the reniform nematode of soybean genotypes derived from crosses with at least one parent resistant to Rotylenchulus reniformis or Heterodera glicynes, or to both. Two experiments in a greenhouse of Embrapa Western Region Agriculture, arranged in a completely randomized design, evaluated 199 genotypes with five replications. Sixty days after artificial inoculation (1000 eggs and larval forms), the nematodes were extracted from the roots and the genotypes evaluated for the number of eggs and larval forms per gram of root (NGR) and for the reproduction factor (RF). Sixty-five genotypes were resistant (RF <1.0), with mean RF significantly equal to M-SOY 8001. The highest number of lines resistant to reniform nematodes, in the different study combinations of crosses, were derived from the genotypes Custer, PI 437654, Fayette, BRSGO Ipameri, BRSMT Pintado, and BRS 262.
Resistance of soybean genotypes to the reniform nematode in a controlled environment
Keywords: Glycine max; Phenotypic characterization; Plant breeding; Rotylenchulus reniformis